Lexical Correspondences between Baram and Thami - Chalise, Krishna Prasad (Nepalese Linguistics, 2022)
Baram and Thami share seventy-two PTB reflexes. Eighteen of them are identical in both languages indicating a higher level of shared retention. Twenty-four of them are identical in Baram and Thami, depicting a higher level of shared innovations. The similarities in the remaining thirty reflexes show the shared retention, and the similar patterns of phonological changes in Baram and Thami present the situation of shared innovations. Twenty similar roots in Baram and Thami, but not Proto-Tibeto-Burman (PTB) reflexes, present further evidence of shared innovations. All the pieces of evidence justify the very close genetic affinity between Baram and Thami.